Current status of clinical studies of IgA nephropathy with minimal proteinuria - SHI Yu-zhen; DONG Li-ting; ZHU Min-min; MA Zhi-gang (Linchuang shenzangbing zazhi)
Patients with IgA nephropathy with minimal proteinuria(proteinuria <1 g/24 h) were previously believed to have good long-term prognosis and a low proportion of renal biopsy, and they generally did not receive active and effective treatment. However, in recent years more and more studies have shown that the long-term prognosis of patients with IgA nephropathy with minimal proteinuria is not optimistic, so it is necessary to improve the understanding about IgA nephropathy with minimal proteinuria. This article reviews the clinical manifestations, renal pathology, treatment and prognosis of IgA nephropathy with minimal proteinuria.